Treatment of oilfield wastewater using microorganisms isolated from budu based production - Ezhar, Nur Izzah (2014)
This study aimed to use crude oil degrading bacteria isolated from Malaysian traditional salt food product (Budu) for biological treatment of oilfield wastewater. Out of five species observed, two species showed dominant growth and have been successfully isolated. Both species are proven to be able to utilize crude oil as sole carbon source and shown to have salt tolerance up to 7.5% NaCl. The species identified were Staphylococcus Hominis sp. and Corynebacterium Auris sp. Preliminary study of oilfield wastewater treatment by mixed culture of Staphylococcus Hominis sp. and Corynebacterium Auris sp. has been evaluated by acclimatizing it with real oilfield wastewater. It takes about 21 days for the mixed culture to acclimatize to the new environment. This study also evaluates the kinetic growth of mixed bacterial culture during the acclimatization process. Based on the graph of specific growth rate (μ) versus substrate plotted, the curve obtained agreed with the Monod equation evaluation. The maximum specific growth rate (μmax) and half saturation constant (Ks) value obtained were 0.328 d-1 and 0.171 mg/L, respectively. A lab scale sequencing batch reactor (SBR) with a volume of 2L was applied in this study to investigate the removal efficiency of chemical oxygen demand (COD) and oil and gas (O&G) based on four different hydraulic retention times (HRT) of 24 h, 36 h, 48 h and 60 h. Influent COD was recorded in the range of 2300 – 2500 mg/L while influent O&G was in the range of 12.4 – 13.2 mg/L. During the SBR treatment, the pH value recorded was in the range of 8.0 – 9.0. Out of four HRTs operated, the longest HRT (60 h) showed the highest removal efficiency of COD and O&G (76.8% and 75.1% respectively). Initial MLVSS operated with 60 h HRT was 1060 mg/L and then increased to 3100 mg/L, approximately 3 times its initial value. An investigation on the hydrocarbon degradation of oilfield wastewater was also carried out. Gas chromatography mass spectrometer was used to analyze the percentage of hydrocarbon degradation. The mixed culture of Staphylococcus Hominis sp. and Corynebacterium Auris sp. shown to be able to degrade C10 – C19 n-alkanes. The percentage of hydrocarbon degradation decreased as the molecular weight of n-alkanes increased. At 60 h HRT, more than 90% hydrocarbon degradation was achieved for C10-C14. As the hydrocarbon chain increase from C15-C19, the percentage of hydrocarbon degradation decreased to 70%. Besides, Staphylococcus Hominis sp. and Corynebacterium Auris sp. were also found to be able to degrade low molecular weight aromatic compound such as ethylbenzene, 2 isomers of xylene (m-xylene and p-xylene), methyl phenol, naphthalene, and methyl naphthalene effectively at 60 h HRT. The degradation percentage recorded at 60 h HRT for ethylbenzene, m-xylene and p-xylene was 85.2%, 88.6%, 85%, 95.4% and 90.8% respectively.